KEPEDULIAN SOSIAL PASCA KONFLIK: MAMALA-MORELA DALAM PENDEKATAN COMMUNITY DEVELOPMENT (STUDI EVALUASI PADA ORGANISASI PERSATUAN ANAK MUDA MALUKU - PAMM) - Lestari, Rini Puji; Rahakbauw, Nancy (Istek Widuri Jakarta, 2019)
This study aim to know and analyze about how Social Concern in Post Conflict by PAMM at Village Mamala and Village Morela in Community Development Approach. Metodology used in this study is qualitative research in evaluation studies by using observation, interview and literature study to obtain to necessary data.The result of the evaluation study research shows the action by Social Concern by PAMM land to the community post conflict at Village Mamala and Village Morela went smoothly and people took it well. But seen from side of social worker, Community Development aproach has not been to good, because PAMM is not a profession organization, most the activities undertaken still nature of social action mediocre and not very serious in the development concept, so that effectiviness and the efficiency of the results of the activitiesare not so influential in orde to restore their social functioning in improving the social welfare state.